Teknik Pengemasan dan Labeling Produk Olahan Makanan Ringan di Desa Pematang Gajah - Sophia; Epit Erwandri; Firna Varina (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Good and attractive product packaging and labeling techniques are needed to support a food product. Not all food business actors such as Micro, Small and Medium Enterprises (MSMEs) can apply modern packaging techniques. Until now, product packaging techniques are still a problem for food businesses, especially Micro, Small and Medium Enterprises. Problems regarding product packaging and labels become obstacles for the development or progress of a business. The problem that occurs in snack business actors in Pematang Gajah Village is that business actors do not know how to package products in an attractive way so that buyers can easily recognize them. The purpose of community service activities is to transfer packaging knowledge and technology so that production is easy to market. This community service activity takes the form of mentoring, counseling and training for micro-entrepreneurs processing snacks, such as sweet potato chips, banana chips, peanut brittle and fish crackers in Pematang Gajah Village, Jambi Outer City District, Muaro Jambi Regency. Product packaging functions as a means of protecting the product and increasing the attractiveness of the product in the market, while labeling functions as the identity of a product so that consumers can choose the right product.